2022
DOI: 10.1097/ta.0000000000003648
|View full text |Cite
|
Sign up to set email alerts
|

Developing a National Trauma Research Action Plan: Results from the acute resuscitation, initial patient evaluation, imaging, and management research gap Delphi survey

Abstract: BACKGROUND: Injury is the leading cause of death in patients aged 1 to 45 years and contributes to a significant public health burden for individuals of all ages. To achieve zero preventable deaths and disability after injury, the National Academies of Science, Engineering and Medicine called for the development of a National Trauma Research Action Plan to improve outcomes for military and civilian trauma patients. Because rapid resuscitation and prompt identification and treatment of injuries are critical in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…While evidence for the safety and efficacy of routine thromboprophylaxis implementation has grown, assessment of the impact of the various implementation interventions has lagged in all patient populations. 44 The trauma patients as a group are different from the average medical population who are included in many implementation studies. Trauma patients often have low socioeconomic status, high-risk occupational exposures and health behaviors, and lower educational background and are at high risk for racial disparity.…”
Section: Evidence Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…While evidence for the safety and efficacy of routine thromboprophylaxis implementation has grown, assessment of the impact of the various implementation interventions has lagged in all patient populations. 44 The trauma patients as a group are different from the average medical population who are included in many implementation studies. Trauma patients often have low socioeconomic status, high-risk occupational exposures and health behaviors, and lower educational background and are at high risk for racial disparity.…”
Section: Evidence Gapmentioning
confidence: 99%
“…While evidence for the safety and efficacy of routine thromboprophylaxis implementation has grown, assessment of the impact of the various implementation interventions has lagged in all patient populations 44 . The trauma patients as a group are different from the average medical population who are included in many implementation studies.…”
Section: Evidence Gapmentioning
confidence: 99%
“…14,15 The methodology used by the National Trauma Research Action Plan (NTRAP) panels is described in previous publications. [16][17][18][19][20][21][22] In brief, an Internet-based program, Surveylet (Calibrum, Saint George, UT; https://calibrum.com), was used to administer the Delphi surveys. In Round 0 of this survey, panelists received lists of themes and specific topics related to trauma systems that had been created by the panel leaders and vetted by the NTRAP Steering Committee.…”
Section: Internet-based Delphi Methodologymentioning
confidence: 99%
“…Practice variation persists owing to clinical uncertainty and barriers to implementing best-practice prevention into routine clinical care. Costantini et al 63 described results from a consensus process called the National Trauma Research Action Plan, which has already identified four major research gaps of high priority in the area of VTE: (1) implementation of early best-practice VTE prevention, (2) timing of initiation of VTE prophylaxis in patients with high-risk injuries, (3) approaches to optimizing VTE prophylaxis, and (4) evaluating use of novel pharmacologic agents for VTE prophylaxis.…”
Section: Deriving Consensus On Future Research Directionsmentioning
confidence: 99%